ANALISIS KINERJA LULUSAN PROGRAM STUDI MANAJEMEN PENDIDIKAN - Nur Yunisah Ahmad; Sitti Roskina Mas; Arifin Suking (Equity In Education Journal, 2022)
This study aims to determine the performance of graduates of the UNG Education Management Study Program in Bone Bolango Regency, in terms of:  (1) Integrity (ethics and morals); (2) Expertise based in the field of science (professionalism); (3) Foreign language skills (English); (4) Ability to use information technology: (5) Ability to communicate; (6) Team cooperation ability; (7) Self-development ability. This study applied a quantitative method with a descriptive approach. The number of research subjects was 30 graduate users. Data collection techniques use a questionnaire. The analytical technique used in this research is the descriptive analysis technique using the percentage formula. The results showed that the responses of graduate users on the aspects of: (1) Integrity (ethics and morals) were in a good category; (2) Expertise based on the field of science (professionalism) was in a good category; (3) Foreign language skills (English) was in a very poor category; (4) The ability to use information technology was in a fairly good category; (5) The communication ability was in a good category; (6) The ability of teamwork was in a good category; (7) Self-development ability was in a good category.